The effect of earplug intervention on temporary threshold shift among small-scale metal workers in Dar es Salaam, Tanzania - Edson M Protas; Simon Lwaho; Evaline Asenga; Witness J Axwesso; Israel P Nyarubeli; Alex M Tungu; Simon Mamuya (Annals of Work Exposures and Health, 2026)
Abstract Background Workers in small-scale metal industries in Tanzania are exposed to hazardous noise levels above 85 dB(A) without hearing protection, risking temporary threshold shift (TTS), a reversible precursor to permanent hearing loss. Objective To determine the prevalence of TTS and evaluate the efficacy of earplug intervention among small-scale metal workers in Dar es Salaam, Tanzania. Methods A pre–post intervention study was conducted from January to April 2024 with 55 workers from 2 small-scale metal industry cooperatives in Dar es Salaam, Tanzania, where noise levels exceeded 85 dB(A). Participants underwent baseline audiometry without hearing protection, followed by a 1-mo earplug intervention and post-intervention testing. Pure-tone audiometry was performed using an Interacoustics AD226 diagnostic audiometer in a mobile soundproof booth. The primary outcome was TTS ≥10 dB at 4 kHz. Data were analyzed using R software (version 2023.12.1 + 402). Continuous TTS values (in dB) were analyzed using paired t-tests. The binary outcome of experiencing a temporary threshold shift (TTS) of ≥10 dB was analyzed using McNemar's test. Results are reported as mean differences, odds ratios, and 95% confidence intervals. Results Before intervention, 27.3% of workers experienced TTS ≥10 dB at 4,000 Hz. Following the earplug intervention, this proportion was 12.7% (P = 0.080). The mean TTS at 4,000 Hz decreased from 1.6 to −1.3 dB (P = 0.082). Changes in mean TTS were also observed at 1,000 Hz (0.3 dB to −1.6 dB, P = 0.016) and 3,000 Hz (1.9 dB to −1.4 dB, P < 0.001). Conclusion Earplug use substantially reduced temporary threshold shifts, demonstrating effectiveness as a practical intervention in small-scale metal industries. These findings support hearing protection integration in small-scale metal industries in informal sector.